Penguatan Kapasitas Pengusaha Perempuan "Pawon Akbar" untuk Mewujudkan Digital Entrepreneurship - Feranita , Nungky Viana; Ulfa , Shinta Fauziah; Agustin , Karina (Dedication : Jurnal Pengabdian Masyarakat, 2026)
The development of digital technology opens up significant opportunities for MSMEs, but women entrepreneurs still face limitations in technology literacy and utilization. This Community Service activity aims to strengthen the capacity of Pawon Akbar's women entrepreneurs in realizing digital entrepreneurship. Implementation methods include outreach, training, and mentoring on product packaging using vacuum sealers, Google Maps registration, WhatsApp Business account creation, and QRIS digital payment implementation. The activity results indicate an increase in partners' digital knowledge and skills as well as optimization of production, marketing, and business management aspects. Evaluation was conducted by comparing conditions before and after the program. The activity outputs include more hygienic product packaging, digital business visibility, and a cashless payment system. This activity was concluded to be effective in increasing the independence and competitiveness of women entrepreneurs in a sustainable manner.